Geologia, petrografia e geoquímica do granito anorogênico Bannach, terreno granito-Greenstone de Rio Maria, PA - ALMEIDA, José de Arimatéia Costa de (Universidade Federal do Pará, 2019)
The Bannach Granite is intrusive in Archean rocks of the Rio Maria Granite -Greenstone Terrane, located in the eastern border the Amazonian craton. This Paleoproterozoic, elliptic, anorogenic granitic batholith is composed essentially of monzogranites with alkali feldspar, quartz and plagioclase as essencial minerals; hornblende, biotite and sometimes clinopyroxene as main mafic minerals; titanite, allanite, apatite, zircon, ilmenite and magnetite as primary accessory minerals; chlorite, sericite-muscovite, carbonate ± fluorite as secondary accessory minerals. Textural and mineralogical characteristics allow to recognize eight varieties of granite: coarse-grained facies bearing amphibole, biotite and sometimes clinopyroxene [cumulatic granite (CG), biotite-amphibole-monzogranite (BAMzG), and amphibole- biotite-monzogranite (ABMzG)]; porphyritic facies with biotite [porphyritic biotite-monzogranite (PBMz)] and leucomonzogranitic fácies [coarse -grained leucomonzogranite (CLMz), early and late medium - evengrained monzogranite (EMLMz and LMLMz) and fine- evengrained monzogranite (FLMz)]. The facies distribution within the batholith is zoned, with the less evolved facies (GC and BAMzG) situated along the border of the body and the more evolved ones in its central portion (LMLMz and CLMz). The Bannach batholith is subalkaline, metaluminous to peraluminous. K 2 O/Na 2 O ratios are between 1 and 2 and FeO t /(FeO t + MgO) between 0.86 and 0.97. The different facies have similar rare earth elements (REE) patterns, being enriched in light REE, slightly depleted in heavy REE and showing a negative europium anomaly that increases from the less evolved to the more evolved facies. The several facies of the Bannach granite plot in the within -plate granite field, as defined by Pearce et al. (1984) for Phanerozoic granites, and into the field of A -type granite, as defined by Whalen et al. (1987). They also show geochemical affinities with the ferroan granites of Frost et al. (2001) and with the A2-subtype (Eby 1992). All facies of the Bannach pluton display high magnetic susceptibility (MS), decreasing regularly from the facies carrying amphibole, biotite ± clinopyroxene (GC and BAMzG) to the leucogranites (EMLMz, CLMz, LMLMz and FLMz ). The different facies of the Bannach granite evolved through fractional crystallization of ferromagnesan minerals and feldspars. The differentiation trend was in the sense: BAMzG- ABMzG-PBMz-EMLMz-CLMz-FLMz. The LMLMz facies is interpreted as a separate intrusion